Growth and survival of Collosoma sp. larvae at different water exchange rate in recirculating aquaculture system - . Sabariah (Jurnal Akuakultur Indonesia)
Recirculating aquaculture system (RAS) is one of aquaculture systems that aimed at providing good water quality as fish culture medium. The objective of this study was to examine the effect of water exchange rate in RAS on the growth and survival of Collosoma sp. Four different water exchange rates were tested, i.e. 0.003 ℓ/s, 0.005 ℓ/s, 0.008 ℓ/s, and 0.010 ℓ/s. Collosoma sp. larvae was stocked at a density of 50 fish/ℓ in plastic jar with a volume of 4ℓ. The observation showed that water exchange rate of 0.005 ℓ/s resulted in the best survival and growth.